Modelo de Responsabilidad Social Empresarial y Condiciones laborales para la empresa Cream Aventurate de la provincia de Cotopaxi - Ecuador - Farinango Conlago, Erika Yosseth (2022)
The objective of this project is to develop a Corporate Social Responsibility (CSR) model to improve working conditions for the company Cream Aventurate in the province of Cotopaxi, Latacunga canton, Joseguango Bajo parish, in order to answer the question: How to implement CSR strategies using ISO 26000, ¿to achieve adequate working conditions in the company Cream Aventurate? Strategies based on the ISO 26000 CSR Standard are proposed, for which a quantitative research process was carried out, correlational scope, which allowed characterizing each of the dimensions, then using the survey technique, the information could be collected through the ISO 26000 Standards instrument. Its evidenced his reliability by Cronbach's Alpha Coefficient with 0.925. Subsequently, dimensions such as Work and labor relations 6,08%, Working conditions and social protection 7,56%, Social Dialogue 3,70%, Occupational health and safety 5.85%, and Human development and training 10% were identified, and a degree of corporate social responsibility of 33.20%. Among the results obtained, it can be mentioned that there is a direct correlation, but most of the items have a slight relationship, which leads to low responsibility. Therefore, the proposed strategies will help to improve working conditions, under an ethical guideline that will allow the company to perform in the best way in the different aspects of the environment, improving the corporate image, increasing the level of commitment of employees in such a way as to obtain the ability to position itself in the market, ensuring the economic growth of the company.